Penyelesaian Wanprestasi Dalam Perjanjian Kredit Dengan Jaminan Hak Tanggungan (Studi Kasus di PT. Bank Capital Indonesia TBK. Cabang Surakarta - Putri, Tia Bethari, Septarina Budiwati, S.H., M.H., CN (2017)
This study aims to determine the settlement procedures of default in the credit agreement to guarantee security rights in PT. Bank Capital Indonesia Tbk. Surakarta branch and explain the problems that arise in tort settlement procedures in the credit agreement with the guarantee of the right of dependents and the way to resolve it. According to the research settlement procedures of default in the credit agreement with the guarantee of the security rights to do with the rare give advance warning letter, if it can not be given a summons letter and if it still can not then be executed. Execution can be through execution under hand or in the execution of the auction through the State Property Office and Auction. Problems that arise are difficult to contact the debtor, the debtor fled or moved domicile, the debtor filed a lawsuit over the auction execution encumbrance, and the debtor would not vacate the auction object.